An Overview of Environmental Education for Millennial Visitors in Indonesian Botanic Gardens - Rosniati A Risna; Anggun R Gumilang (The East Java Biological Society, 2019)
In an attempt to meet the information and education needs of millennial visitors – the new tourism frontiers – in industrial revolution 4.0 era, environmental education program in Indonesian Botanic Gardens (IBGs) has applied a new paradigm. As the world become more digital, the IBGs has also developed more digital programs in terms of environment, biology and conservation education. There are mobile apps for self-guided tours, digital class for various topics related with horticulture practices, virtual adventurous games, online reservation, are to name some. Annual numbers of IBGs visitors showed increasing trends in period of study, which was probably caused by increasing quality of information, education program, digital facilities, and displays, including photo spots. This paper will describe how IBGs play important role in supporting the Sustainable Development Goals (SDGs) in quality education, as well as Target 14 of Global Strategy for Plant Conservation (GSPC) by making more engagement with millennial visitors.